Effects of Ramadan fasting toward stress using the DASS-42 scoring system / Sayid Ridho and Akbar Maulana AK - Ridho, Sayid; AK, Akbar Maulana (Universiti Teknologi MARA, 2023)
Problems in college faced by students can cause stress. Ramadan fasting is beneficial for physical, psychic, and emotional health, among which it can reduce stress. This study aimed to understand the effect of Ramadan fasting on stress of preclinical medical students at UIN Syarif Hidayatullah Jakarta. The design of this study was prospective cohort analytic with a cross-sectional approach with a one group pre-test and post-test design. The consecutive sampling method was used for 242 respondents. To collect the data, the DASS-42 questionnaires are used. The Wilcoxon test were used to analyse the data. We found that 52 (21.5%) were experiencing stress while 190 (78.5%) were normal. The findings revealed that the stress scores fell during the pre-to post-Ramadan period for all subjects (p=0.000) either stress (p=0.000) or normal students (p=0.000). Based on the results, we found that Ramadan fasting can affect the stress scores of preclinical medical students in both normal and stressful students.